Designing a National Scientific and Technological Communication System : The SCATT Report - Ackoff, Russell L. (University of Pennsylvania Press, 1976)
Contributors: Russell L. Ackoff, Martin C. J. Elton, Thomas A Cowan, James C. Emery, Peter Davis, Marybeth L. Meditz, Wladimer M. Sachs. With the collaboration of William C. Donovan, Mohammad Jahani, and Jonathan V. Rosenhead.